Mind Matters in Investments: Unveiling the Psychological Forces Shaping Decision Making Behavior - Helmina, Monica Rahardian Ary; Rosari, Novika; Yusniar, Meina Wulansari; Utaminingsih, Nanik Sri (JDM (Jurnal Dinamika Manajemen), 2023)
The Indonesian Central Securities Depository (KSEI) in 2021 revealed a significant increase in the number of capital market investors. This study aims to analyze the psychological and gender biases influencing capital market investors in making risky investment decisions, based on the theory of myopic loss aversion (MLA). The participants two groups: experienced and inexperienced investors. The experimental stage involved manipulating the groups with two types of treatment, frequent and infrequent, using a between-within-subject design with a 2 x 2 factorial structure. The results of the gender experiment showed that male and female participants in the experienced group exhibited similar levels of courage. However, in the inexperienced group, which mainly consisted of students, gender differences were observed. Men tended to be more daring and speculative in their decision-making, particularly during the pandemic. On the other hand, women tended to prioritize security in their investment choices. Additionally, the study found evidence of a “shock effect” experienced by participants during the experiment. This effect contributed to investors’ cautious decision-making, and it was also influenced by gender differences. The findings suggest Man in the inexperienced group displayed higher risk-taking tendencies compared to women, who were more focused on security when using their investment funds.